Distribution of trace metals (Cu, Pb, Ni, Zn) between particulate, colloidal and truly dissolved fractions in wastewater treatment. (May 2017) - Hargreaves, Andrew J.; Vale, Peter; Whelan, Jonathan; Constantino, Carlos; Dotro, Gabriela; Campo, Pablo; Cartmell, Elise
Abstract: The distribution of Cu, Pb, Ni and Zn between particulate, colloidal and truly dissolved size fractions in wastewater from a trickling filter treatment plant was investigated. Samples of influent, primary effluent, humus effluent, final effluent and sludge holding tank returns were collected and separated into particulate (i.e. > 0.45 μm), colloidal (i.e. 1 kDa to 0.45 μm), and truly dissolved (i.e. < 1 kDa) fractions using membrane filters. In the influent, substantial proportions of Cu (60%), Pb (67%), and Zn (32%) were present in the particulate fraction which was removed in conjunction with suspended particles at the works in subsequent treatment stages. In final effluent, sizeable proportions of Cu (52%), Pb (32%), Ni (44%) and Zn (68%) were found within the colloidal size fraction. Calculated ratios of soluble metal to organic carbon suggest the metal to be adsorbed to or complexed with non-humic macromolecules typically found within the colloidal size range. These findings suggest that technologies capable of removing particles within the colloidal fraction have good potential to enhance metals removal from wastewater. Highlights: Distribution of Cu, Pb, Ni and Zn in particle size fractions of wastewater studied. Sizeable amounts of metals remained in the colloidal fraction following treatment. Metals are mainly adsorbed/complexed with organics found in the colloidal fraction. Colloid removal technologies have potential for metals elimination from wastewater.